Design and performance of the LHCb trigger and full real-time reconstruction in Run 2 of the LHC - Aaij, Roel; D'Argent, Philippe; Kopecná, Renata; Neubert, Sebastian (Journal of Instrumentation, 2019)
The LHCb collaboration has redesigned its trigger to enable the full offline detector reconstruction to be performed in real time. Together with the real-time alignment and calibration of the detector, and a software infrastructure to make persistent the high-level physics objects produced during real-time processing, this redesign enabled the widespread deployment of real-time analysis during Run 2. We describe the design of the Run 2 trigger and real-time reconstruction, and present data-driven performance measurements for a representative sample of LHCb's physics programme.
Gesehen am 26.03.2020